2021
DOI: 10.1128/aac.00863-20
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Trends of Zoliflodacin against Multidrug-Resistant Neisseria gonorrhoeae Clinical Isolates in Nanjing, China, 2014 to 2018

Abstract: Previously, we reported potent activity of a novel spiropyrimidinetrione, zoliflodacin, against N. gonorrhoeae isolates from symptomatic men in Nanjing, China, collected in 2013. Here, we investigated trends of susceptibilities of zoliflodacin in 986 isolates collected from men between 2014 and 2018. N. gonorrhoeae isolates were tested for susceptibility to zoliflodacin and seven other antibiotics. Mutations in gyrA, gyrB, parC, parE and mtrR genes were determined by PCR and sequencing. The MICs of zoliflodaci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Thus, the GyrB S467N substitution appears to predispose to emergence of zoliflodacin resistance, despite not conferring resistance to zoliflodacin on its own. Fortunately, N. gonorrhoeae strains with GyrB S467N substitution appear to be very rare internationally ( https://pathogen.watch/collections/all?organismId=485 ; Le et al, 2021 ). Furthermore, the zoliflodacin-resistant SE600/18-D429N mutant suffered from a biofitness disadvantage and was outcompeted by the zoliflodacin-susceptible parent SE600/18 strain, which suggests that these zoliflodacin-resistant strains will be less effective at amplifying and spreading after emergence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the GyrB S467N substitution appears to predispose to emergence of zoliflodacin resistance, despite not conferring resistance to zoliflodacin on its own. Fortunately, N. gonorrhoeae strains with GyrB S467N substitution appear to be very rare internationally ( https://pathogen.watch/collections/all?organismId=485 ; Le et al, 2021 ). Furthermore, the zoliflodacin-resistant SE600/18-D429N mutant suffered from a biofitness disadvantage and was outcompeted by the zoliflodacin-susceptible parent SE600/18 strain, which suggests that these zoliflodacin-resistant strains will be less effective at amplifying and spreading after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…However, in static in vitro laboratory experiments zoliflodacin-resistant mutants have been selected; all containing substitutions of amino acids D429 or K450 of GyrB ( Alm et al, 2015 ; Foerster et al, 2015 ; Foerster et al, 2019 ; Jacobsson et al, 2021 ). No clinical isolate with amino acid substitution in GyrB K450 and only one single clinical isolate with a GyrB D429V substitution has been found ( Jacobsson et al, 2014 ; Alm et al, 2015 ; Unemo et al, 2015 ; Unemo et al, 2019 ; Bradford et al, 2020 ; Le et al, 2021 ; Adamson et al, 2021 ). Additionally, an isolate with a GyrB S467N substitution was selected previously in static in vitro experiments ( Alm et al, 2015 ) .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, studies revealed that the conventional therapeutic dose of 2 g does not induce cardiac arrhythmias and is well tolerated [ 137 ]. Although zoliflodacin maintains an excellent in vitro activity against clinical N. gonorrhoeae isolates, the rising potential to develop AMR led to further antibiotics research [ 138 ]. A 2021 study found that a single dose of MBX-4132, an acylaminooxadiazole that selectively inhibits ribosomal trans-translation, successfully cleared MDR N. gonorrhoeae infection in mice [ 139 ].…”
Section: Novel Drugs and Nano Moleculesmentioning
confidence: 99%